Moderate-to-vigorous intensity physical activity among adolescents in the USA during the COVID-19 pandemic - Nagata, Jason M.; Cortez, Catherine A.; Dooley, Erin E.; Iyer, Puja; Ganson, Kyle T.; Pettee Gabriel, Kelley (Preventive medicine reports, 2022)
•The study examined adolescents’ physical activity during the COVID-19 pandemic.•Median moderate-to-vigorous physical activity was 2 h per week.•8.9% met physical activity guidelines during the pandemic compared to 16.1% before.•Poor mental health, worry, and stress were associated with lower physical activity.•Higher coping and social support were associated with higher physical activity. This study aimed to evaluate adolescents’ moderate-to-vigorous intensity physical activity (MVPA) during the COVID-19 pandemic with regards to sociodemographic characteristics and determine mental health and resiliency factors associated with MVPA among a diverse national sample of adolescents ages 10–14 years. Data were collected during the pandemic in May 2020 from the Adolescent Brain Cognitive Development Study (ABCD, N = 5,153), a national prospective cohort study in the U.S. MVPA was quantified as the product of reported duration and frequency (hours per week), which was further summarized as the proportion meeting age-appropriate 2018 Physical Activity Guidelines for Americans. A similar estimate was generated using MVPA data collected prior to the pandemic. Mental health and resiliency measures were collected during the pandemic. Regression models examined associations between mental health or resiliency measures and MVPA during the pandemic. Median MVPA was 2 h per week (IQR 0, 6). Overall, the percentage of the cohort meeting MVPA guidelines decreased from 16.1% (pre-pandemic) to 8.9% (during the pandemic). Racial/ethnic minority adolescents and adolescents from lower socioeconomic backgrounds were significantly less likely to meet MVPA guidelines during the pandemic. Poorer mental health, COVID-related worry, and stress were associated with lower MVPA, while more social support and coping behaviors were associated with higher MVPA during the pandemic. In this large, national sample of adolescents, the proportion of those meeting MVPA Guidelines was lower during the COVID-19 pandemic, with significant disparities by race/ethnicity and socioeconomic status. Interventions to promote social support and coping behaviors may improve MVPA levels among adolescents during the pandemic.